Euthanasie met Barbara en Stefanie. - Claes, Barbara, 1983-; Claes, Stefanie, 1983- (Amsterdam : De Nieuwe Toneelbibliotheek, 2017)
Toneelstuk over oud worden, zin van het leven, lichamelijk aftakelen, ...